Diagnostic Accuracy of Ultrasound Scanning for Prenatal Microcephaly in the context of Zika Virus Infection: A Systematic Review and Meta-analysis - Ezinne C. Chibueze (Nature Portfolio, 2017)
Abstract To assess the accuracy of ultrasound measurements of fetal biometric parameters for prenatal diagnosis of microcephaly in the context of Zika virus (ZIKV) infection, we searched bibliographic databases for studies published until March 3rd, 2016. We extracted the numbers of true positives, false positives, true negatives, and false negatives and performed a meta-analysis to estimate group sensitivity and specificity. Predictive values for ZIKV-infected pregnancies were extrapolated from those obtained for pregnancies unrelated to ZIKV. Of 111 eligible full texts, nine studies met our inclusion criteria. Pooled estimates from two studies showed that at 3, 4 and 5 standard deviations (SDs) <mean, sensitivities were 84%, 68% and 58% for head circumference (HC); 76%, 58% and 58% for occipitofrontal diameter (OFD); and 94%, 85% and 59% for biparietal diameter (BPD). Specificities at 3, 4 and 5 SDs below the mean were 70%, 91% and 97% for HC; 84%, 97% and 97% for OFD; and 16%, 46% and 80% for BPD. No study including ZIKV-infected pregnant women was identified. OFD and HC were more consistent in specificity and sensitivity at lower thresholds compared to higher thresholds. Therefore, prenatal ultrasound appears more accurate in detecting the absence of microcephaly than its presence.